The Fate of Visible Features of Invisible Elements - Herzog, Michael H.; Otto, Thomas; Ögmen, Haluk (Frontiers in Psychology, 2012)
To investigate the integration of features, we have developed a paradigm in which an element is rendered invisible by visual masking. Still, the features of the element are visible at other elements (sequential metacontrast). In this sense, we can “transport” features non-retinotopically across space and time. The features of the invisible element integrate with features of other elements if and only if the elements belong to the same spatio-temporal group. In this case, features unconsciously integrate. The mechanisms of this kind of feature integration seem to be quite different from classical mechanisms proposed for feature binding. We propose that feature processing, binding, and integration occur simultaneous during grouping elements into wholes.